Interleukin-18 interacts with NKCC1 to mediate brain injury after intracerebral hemorrhage - Beibei Xu; Hao Li; He Zheng; Zhongyu Gao; Zhigang Miao; Xingshun Xu; Hao Yang; Yi Yang (Brain, Behavior, & Immunity - Health)
Interleukin 18 (IL-18), a proinflammatory cytokine, has been implicated in various neurological disorders, including cerebrovascular disease and psychiatric disorders. In a previous study, IL-18 was observed to activate microglia and enhance the inflammatory response following intracranial hemorrhage (ICH). However, the underlying mechanism remains unclear. In the present study, we found that IL-18 and IL-18 receptor (IL-18 R) are primarily secreted by neurons during the early stages after ICH, with microglia becoming the predominant source at 12–24 h after ICH. Meanwhile, the expression level of IL-18 R increased following ICH, along with an augmentation in the binding affinity of IL-18 R to IL-18. Subsequently, the deficiency of IL-18 R mitigated neurological impairment and subsequent activation of inflammatory pathways in mice post-ICH. Moreover, our findings suggest that IL-18-induced neurological injury after ICH may be mediated by the interaction between IL18R and NKCC1. Significantly, the NKCC1 inhibitor rescued the neurologic injury after ICH. In conclusion, our study suggests that targeting the IL-18/IL-18R/NKCC1 pathway could be an effective therapeutic strategy to attenuate secondary brain injury after ICH.